Optimalisasi Ekowisata Berbasis Kearifan Lokal Sebagai Peningkatan Pendapatan Perempuan Di Daerah Perbatasan - Rissa Ayustia; Jones Parlindungan Nadapdap (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Optimizing ecotourism in the border areas of the Unitary State of the Republic of Indonesia based on local wisdom as an effort to strengthen and increase the role, capacity, and initiative of women as one of the stakeholders in optimizing ecotourism. Ecotourism began to be developed due to the negative impact of conventional tourism activities and the environmental damage caused by business people seeking their own profit without paying attention to environmental sustainability. The purpose of this study is to describe the optimization of ecotourism based on local wisdom so that it can increase women's income. This study uses a descriptive research method with a qualitative approach. The data collection technique used is the technique of Observation, Interview and Documentation. The research location is in Sebente Village, Shout District, Bengkayang Regency, West Kalimantan Province. The research subjects were the Sebente. Village Head, Pokdarwis Chair, PKK Chairmen and members, women who had businesses, and visitors. The results showed that the optimization of ecotourism was carried out by empowering women in tourist villages through local potential and wisdom. This potential is the development capital of the village government so that women can have the ability to manage natural resources to increase production capacity, output, and ultimately improve women's welfare.